A Pediatric Case of Ramsay Hunt Syndrome - Derin, Serhan (Hindawi Publishing Corporation, 2014)
Ramsay Hunt syndrome (RHS) is characterized by facial paralysis, inner ear dysfunction, periauricular pain, and herpetiform vesicles. The reported incidence in children is 2.7/100,000. The pathogenesis involves the reactivation of latent varicella zoster virus (VZV) in the geniculate ganglion of the facial nerve. The recovery rate is better in children than in adults. This paper discusses a 12-year-old girl with a rare case of peripheral facial paralysis caused by RHS and reviews the literature.